The Effects of the Internationalisation of Firms on Innovation and Productivity - SIEDSCHLAG, IULIA; ZHANG, XIAOHENG (KEVIN) (My University, 2010)
This paper examines the effects of the internationalisation of firms via foreign direct investment and trade on their innovation and productivity performance. Our econometric results suggest that foreign affiliates and domestic exporters were more likely to invest in innovation and furthermore that they were more likely to be more successful in terms of innovation output and higher productivity than firms that served only the domestic market. On average, innovation output was positively associated with labour productivity over and above other determinants. Access to external knowledge flows explain to a large extent the innovation performance of firms, in particular co-operation with suppliers, with consultants, commercial labs or private R&D institutes, with universities or other higher education institutions.
PUBLISHED
Keywords: Multinational Firms; Exporting; Knowledge Production; Productivity